Encadenamientos productivos en la industria automotriz latinoamericana - Pinazo, Germán; Toledo, Pablo (Papeles de Europa, 2022)
This paper presents original data on production chains of the Latin American automotive industry (South America and Mexico, more specifically) based on input-output techniques for the year 2017 and, in some cases, for 2007. These data are used to reflect on the problem on the problem of regional productive integration. The article ends with some reflections on the data presented and with comments on possible new lines of research
Keywords: Input-Output; Automotive; Latin America